Factors Related to Duration and Interaction of Doctor-Patient Communication at Diponegoro National Hospital - Kriesye Refertiwi; Teddy Wahyu Nugroho; Saekhol Bakri; Diah Rahayu Wulandari (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Doctor-patient communication is an important foundation in the process of diagnosis, therapy, and prevention of disease. Communication has been a challenge for most doctors. The doctor's willingness to provide sufficient time is needed to establish good interaction and communication between the doctor and the patient. Aim: To determine what factors are related to the duration and interaction of communication between doctors and patients at Diponegoro National Hospital (RSND) Semarang. Methods: Research subjects using analytic survey research designs, with quantitative approaches and cross-sectional research designs. The sample of this study was 80 patients who came to internal, neurological, pediatric, and cardiovascular polyclinics RSND Semarang. The independent variables were factors related to doctor-patient communication (number of patients, type of patients, complexity of the disease, and qualifications of specialist doctors). The dependent variable was doctor-patient communication (duration and communication interaction at RSND Semarang). Results: Most of the respondents (72.5%) experienced < 8 minutes of communication. The number of patients, type of patients (old/new), and qualifications of specialist doctors (internists, neurologists, pediatricians, and cardiologists) were statistically related to the duration of communication (p < 0.005). Meanwhile, the complexity of the disease was not statistically related to the duration of doctor-patient communication (p = 0,416). There was a relationship between the number of patients, type of patients (old/new), and qualifications of specialist doctors to the communication interaction of doctor-patient (p < 0.005). On the contrary, there is no relationship between the complexity of the disease and the communication interaction between the doctor and patient (p = 0,324). Conclusion: Factors related to the duration and communication interaction between doctor and patient at RSND Semarang are the number of patients, type of patients, and qualifications of specialist doctors.